MATHEMATICAL TERMINOLOGY: ON THE NAMES OF FRACTIONS IN THE MACEDONIAN LANGUAGE - Celakoska-Jordanova, Vesna; Celakoska, Emilija (Matematichki Bilten, 2016)
In this note we discuss the question of the names of fractions in the Macedonian language and explain our position in using а consistent system for generating nouns that denotes fractions, a system that is unambiguous and clear, unique and complete.